MICROTEACHING LESSON STUDY: THE EFL STUDENT TEACHERS’ PERCEPTION - Fitri Budi Suryani (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
As a variation of lesson study, microteaching lesson study is applied by student teachers in microteaching course where they practise teaching to their peers or real students. Thus, it incorporates the aspects of microteaching and  lesson study, i.e., the teaching of small group of peers or real students, the shortened length of time for teaching (approximately 25 to 30 minutes), the division of student teachers in group of three, the cycles of collaborative lesson planning, teaching, and reflecting, and the use of video to capture teacher lesson for later analysis. In addition, it encompasses the features of learning to teach such as reflective teaching, classroom research, and action research. In other words, it provides student teachers with environment that might enable them to be adaptive teachers who can adapt and adjust to the complexities of teaching learning activities.This present study aims to investigate the EFL student teachers’ perception of microteaching lesson study. The participants were eighteen EFL student teachers who enrolled in microteaching lesson study course at the English Education Department of Muria Kudus University. The data were gathered using feedback questionnaire on microteaching lesson study adapted from Molina (2012). The findings reveal that the EFL student teachers perceive microteaching lesson study positively.